Estudo biológico e morfométrico dos estádios ninfais de Rhodnius neglectus Lent, 1954 (Hemiptera, Reduviidae) - Ponsoni, E. J. [UNESP]; Marconato, E. [UNESP]; Rosa, João Aristeu da [UNESP] (My University, 2004)
The following parameters of the biological cycle of the Rhodnius neglectus were determined under a temperature of 28°C and relative humidity of the air varying between 52-94%: a) average period of incubation: 13.67 days; b) rate of the eggs eclosion: 86.18%; c) average period of growth of the 1st, 2nd, 3rd, 4th, 5th instar nymphs: 18.91, 15.19, 21.38, 21.34, 30.43 days, respectively; d) percentage of death in the instar nymphs: 13.82, 18.26, 9.95, 8.78, 15.06% respectively; e) percentage of changes per instar nymphs: 86.18, 81.74, 90.05, 91.22, 84.94% respectively. The morphometric study with the stereoscopic microscope and Leica image analyses system, using the Qwin software, of the five instar nymphs showed that in the five instar nymphs a gradual growth of the head, thorax and abdomen occurs. In all the instars the abdomen is the largest segment. In the four first instars the head is larger than the thorax. In the fifth instar the head and the thorax present equivalent sizes.
Biological and morphometrical study of instar nymphs of Rhodnius neglectus Lent, 1954 (Hemiptera, Reduviidae)
Keywords: Biology; Morphometrics; Nymph; Rhodnius neglectus; abdomen; animal tissue; arthropod; biology; computer program; controlled study; death; egg; growth; head; Hemiptera; humidity; image analysis; incubation time; morphometrics; nonhuman; Rhodnius; stereomicroscopy; temperature; thorax